2012
DOI: 10.4103/2277-9175.100197
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preemptive analgesia with celecoxib or acetaminophen on postoperative pain relief following lower extremity orthopedic surgery

Abstract: Background:Efficacy of preemptive analgesia with nonsteroidal antiinflammatory drugs (NSAIDs) in comparison with acetaminophen is controversial. The present study evaluates the preemptive analgesia efficacy of celecoxib and acetaminophen in comparison with placebo for postoperative pain relief in patients who underwent orthopedic surgery under general anesthesia.Materials and Methods:Ninetypatients eligible for elective distal extremity surgery were categorized in three groups: group C includedpatients who rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…In orthopedic surgeries, NSAIDs have been widely used to reduce postoperative pain. Kashefi et al [23] reported that preoperative oral celecoxib at the dose of 200 mg every 2 h could effectively control the postoperative pain in patients who underwent lower extremity orthopedic surgeries. Compared with celecoxib and placebo, etoricoxib was more effective for PA in controlling postoperative pain [24].…”
Section: Nsaidsmentioning
confidence: 99%
“…In orthopedic surgeries, NSAIDs have been widely used to reduce postoperative pain. Kashefi et al [23] reported that preoperative oral celecoxib at the dose of 200 mg every 2 h could effectively control the postoperative pain in patients who underwent lower extremity orthopedic surgeries. Compared with celecoxib and placebo, etoricoxib was more effective for PA in controlling postoperative pain [24].…”
Section: Nsaidsmentioning
confidence: 99%
“…When comparing the use of acetaminophen with celecoxib for preemptive analgesia, celecoxib was superior to acetaminophen for reducing postoperative pain in patients undergoing lower extremity orthopedic surgery (28). …”
Section: Discussionmentioning
confidence: 99%
“…In another article performed by Gunsen et al . [ 22 ] the efficacy of Paracetamol versus Tenoxicam on postoperative pain, after abdominal hysterectomy, was evaluated, and it was found that Tenoxicam was associated with lower pain scores at the second, fourth, sixth, and twenty-fourth hour postoperatively.…”
Section: Discussionmentioning
confidence: 99%